The Top 50 Most Cited Publications in Disability Sport: A Bibliometric Analysis - Khoo, Selina; Li, Chunxiao; Ansari, Payam (SAGE Publications, 2018)
Despite increasing publications in disability sport, no bibliometric analysis has been conducted to evaluate their impact.We conducted a systematic search of theWeb of Science Core Collection citation index on June 26, 2017 for publications published since 1980 to identify the top 50 most cited publications in disability sport. The top 50 cited publications were mainly articles and reviews published in the English language between 1993 and 2014. Most of the 148 authors who contributed to these publications were based in Europe and North America. The majority of the publications can be categorized as sociological and psychological as well as training and competition effects. The most researched events were the Paralympics and Special Olympics. These top-cited publications have contributed to the development of disability sport research.